Integrated Solar-IoT monitoring and predictive maintenance systems for irrigation (S-IoTP) / Hasyiya Karimah Adli ... [et al.] - Adli, Hasyiya Karimah; Ku Husin, Ku Azmie; Wan Salihin Wong, Khairul Nizar Syazwan; Remli, Muhammad Akmal (2021)
S-IoTP is an integrated prototype system of Internet-of-Things (IoT) with auto-tracking solar panel for irrigation. It consists of an auto-track-developed solar panel to power water pump with IoT hardware and software and mobile user interface. The solar panel moves based on the sunlight direction to harvest maximum solar output. With IoT software, real-time data of the solar power output was monitored. The predictive analysis for forecasting solar power output based on modelbased algorithm using Python to ensure sustainable power for electricity, optimise the irrigation process and water consumption. S-IoTP provides a consumer-oriented solar system with affordable cost and energy saving device that fits consumer needs. With S-IoTP, the irrigation cost can be reduced to ±93%, which, the total cost per year for this whole system is RM 1020 only, compared to the traditional process of irrigation which costs RM 16200 per year. To date, the technology readiness level of the S-IoTP is TRL 5, which is in the stage of development and it is validated in relevant environment.